Work engagement of school physiotherapists in special education: The role of school climate and self-efficacy - Korfia, Maria; Touloupis, Thanos; Sofos, Alivisos; Lipourli, Eleni (Psychology: the Journal of the Hellenic Psychological Society, 2025)
The present study investigated the work engagement of school physiotherapists in special education, as well as the role of perceived school climate and self-efficacy in work engagement. Overall, 118 physiotherapists (75% women) from all over Greece, who worked in primary (54%) and secondary schools (46%) of special education, completed electronic self-report scales related to the variables involved. The results showed that physiotherapists’ work engagement (dedication, absorption) ranges at above-average levels (based on the scale’s response system), regardless of gender. Furthermore, the dimensions of the perceived school climate that concerned colleague collaboration, the implementation of educational/therapeutic innovations at school as well as the relationships with the students seemed to positively contribute to physiotherapists’ work engagement. Additionally, physiotherapists’ sense of self-efficacy in terms of collaboration with colleagues and students’ parents, ensuring discipline as well as in terms of mobilizing students and implementing educational adaptations also seemed to positively contribute to physiotherapists’ the work engagement. The findings imply the necessity to intensify/plan school psychoeducational prevention actions aimed at strengthening specific dimensions of the school climate in special education schools as well as physiotherapists’ self-efficacy. These proposed actions may positively contribute to school physiotherapists who work in special education.